How many lawyers does it take to stop the global meltdown: Law as an instrument in the face of climate change? - O’diana Rocca, Richard (2020)
This text seeks to develop the different possibilities that the law offers to influence the right to the environment and combat climate change. In this way, it presents the climate commitments and how these are obligations that States must comply with. Likewise, it studies the environmental legislation in force in Peru, both the positive legislation and that which does not necessarily protect the right to the environment. And, finally, we study the possibility of using strategic litigation at both the national and international level so that citizens themselves can seek to undo situations generated by state or private agents that seek to affect the right to the environment.